OPTIMALISASI PENERIMAAN NEGARA BUKAN PAJAK PADA LEMBAGA PENYIARAN PUBLIK TELEVISI REPUBLIK INDONESIA (LPP TVRI) - Agung Dinarjito (SUBSTANSI, 2017)
Non-tax state revenue (PNBP) is becoming one of the important revenue source besides the tax revenue. Therefore, non-tax revenue optimization becomes very important. In addition, the findings of the Supreme Audit Agency (BPK) on the management of non-tax revenues can make the Ministries / Agencies get disclaimer opinion, one of which is the Public Broadcasting Institution of Televisi Republik Indonesia (LPP TVRI). Findings on the Financial Statements of LPP TVRI PNBP are the levies without any legal basis on receipt of broadcast and non-broadcast services (jasinonsi) and use immediately upon receipt of the jasinonsi. This study aims to give recommendation for LPP TVRI about how to manage non-tax state revenue to avoid disclaimer opinion from BPK. This study is a descriptive qualitative study with normative juridical approach to analyze the problem based on the applicable law and regulations related to non-tax state revenues with the aim to provide recommendations or suggestions to the LPP TVRI so that in the future, the findings will not be repeated. Based on the results of the discussion, LPP TVRI must manage the receipt (PNBP) using the rules relating to state finances (PNBP rules). Therefore, the authors suggest LPP TVRI soon submit proposals Government Regulation on non-tax revenues and then submit the application of the use of funds non-tax revenues to the Finance Minister after the Government Regulation (PP) is determined by the President.